Adsorption of lead(II) from aqueous solution using a poly(ethyleneimine)‐functionalized organic–inorganic hybrid silica prepared by hydrothermal‐assisted surface grafting method. Issue 6 (20th May 2014) - He, Lu; Liu, Dan‐Dan; Wang, Bing‐Bing; Xu, Hong‐Bo
ABSTRACT The poly(ethyleneimine) (PEI)‐functionalized organic–inorganic hybrid silica was prepared by a hydrothermal‐assisted surface grafting technique. Static adsorption experiment results showed that PEI‐functionalized hybrid silica had high static adsorption capacity of 68.1 mg g−1, which was 1.3 times as much as that of the sorbents by conventional heating method. PEI‐functionalized hybrid silica displayed stable adsorption ability for Pb(II) ions in the range of pH 4–8. An equilibrium state was reached within 30 min. Freundlich and Langmuir adsorption isotherm models were used to fit the equilibrium data, and it was found that the Langmuir adsorption model provided good fit. Kinetic studies indicated that the adsorption followed a pseudo‐second‐order model. Various thermodynamic parameters, such as ΔGo, ΔHo and ΔSo, were evaluated with results indicating that this system was a spontaneous and endothermic process. The results indicated that PEI‐functionalized hybrid silica could be employed as an effective material for the adsorption of Pb(II) ions from aqueous solutions. © 2014 Curtin University of Technology and John Wiley & Sons, Ltd.